Specialised computer simulator "SimEnPhysiol" - Grygoryan, R.D.; Aksonova, T.V.; Degoda, A.G. (Інститут програмних систем НАН України, 2018)
A specialized software simulator (SSS) is described. SSS simulates the human physiological complex reactions to the appearance of energy shortages (ATP molecules) in cells. SSS is based on mathematical models, representing multilevel physiological mechanisms that provide a long-term balance of energy in each cell of the body. The key to creating the SSS is a binary model that ignores the specialization of the cell and reduces them to two virtual cells differed them only by their energy status – a balanced cell or a cell experiencing energy deficit. Both the autonomous mechanisms (AM) of cells and multicellular local and general physiological mechanisms are modelled. It is assumed that under incapacity of the AM, the cell having an energy deficit activates the multicellular physiological mechanisms to restore the disturbed energy balance. In fact, the help of the mechanisms of the organism to cellular mechanisms is provided through regulators based on negative feedback. The SSS allows one to simulate every dynamic load on the virtual cell and to evaluate the contribution of each of the physiological regulators in counteracting the energy deficit in the virtual cell. The results of test studies are presented. The physiologist-researcher aimed SSS is implemented in the software technology DOT.NET, and is autonomous for use on a PC.Problems in programming 2018; 2-3: 280-287